Factor H‐related protein 1: a complement regulatory protein and guardian of necrotic‐type surfaces. (23rd December 2020) - Skerka, Christine; Pradel, Gabriele; Halder, Luke D.; Zipfel, Peter F.; Zipfel, Svante L.H.; Strauß, Olaf
Abstract : Factor H‐related protein 1 (FHR‐1) is a member of the factor H protein family, which is involved in regulating innate immune complement reactions. Genetic modification of the encoding gene, CFHR1 on human chromosome 1, is involved in diseases such as age‐related macular degeneration, C3 glomerulopathy and atypical haemolytic uraemic syndrome, indicating an important role for FHR‐1 in human health. Recent research data demonstrate that FHR‐1 levels increase in IgA nephropathy and anti‐neutrophilic cytoplasmic autoantibodies (ANCA) vasculitis and that FHR‐1 induces strong inflammation in monocytes on necrotic‐type surfaces, suggesting a complement‐independent role. These new results increase our knowledge about the role of this complement protein in pathology and provide a new therapeutic target, particularly in the context of inflammatory diseases induced by necrosis. This review summarizes current knowledge about FHR‐1 and discusses its role in complement reactions and inflammation. Linked Articles: This article is part of a themed issue on Canonical and non‐canonical functions of the complement system in health and disease. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.14/issuetoc